2020
DOI: 10.1021/acsanm.0c00435
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Host–Guest Interactions between Cucurbit[7]uril and Guests on Gold Surfaces for Rational Engineering of Gold Nanoparticles

Abstract: Although macrocyclic host engineered nanoparticles have drawn a lot of attention in the past decade, little attention was paid to the binding affinity between the host and guest assembled on nanoparticles. In this work, the interactions between cucurbit[7]­uril (CB[7]) and three guests with phenyl (1), adamantyl (2), and ferrocene (3) groups on a gold surface were investigated. Their interactions were classified into four groups. The binding constants between CB[7] and three guests in the solution (group I) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…S1, ESI †). 30 Although the values of the binding constants measured using SMFS differed greatly from those measured via NMR, they displayed the same tendency. In addition, the binding constants of G1-4 with CB [8] were calculated to be 4-6 times greater than G1-4 without CB [8], leading to an increase in the rupture forces of G1-4 before and after CB [8] addition.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…S1, ESI †). 30 Although the values of the binding constants measured using SMFS differed greatly from those measured via NMR, they displayed the same tendency. In addition, the binding constants of G1-4 with CB [8] were calculated to be 4-6 times greater than G1-4 without CB [8], leading to an increase in the rupture forces of G1-4 before and after CB [8] addition.…”
mentioning
confidence: 89%
“…29 Cucurbiturils (CB[n]s) can also form a well-defined self-assembled monolayer (SAM) on substrates, and their disassociation with guests has recently been determined by us and other groups. 30,31 SMFS results suggested that hydrophobic and ion-dipole interactions may dominate the separation process between charged guest molecules and CB [7], which cannot be addressed via bulk measurements.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, interactions of gold nanoparticles with various host and guest systems have been determined by using cyclic voltammetry, [15] isothermal titration calorimetry, [16] and singlemolecule force spectroscopy. [17] In this work, for the first time we utilize Hamilton receptor and cyanurate guest molecules to study the host-guest interactions on the surface of functionalized SPIONs (Scheme 1). We prepare two types of nanoparticles bearing either the Hamilton receptor (Fe 3 O 4 @HamPAc) or the cyanurate derivative (Fe 3 O 4 @CyaPAc) and investigate how the position of the interacting molecules affects the overall binding events on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, interactions of gold nanoparticles with various host and guest systems have been determined by using cyclic voltammetry, [15] isothermal titration calorimetry, [16] and single‐molecule force spectroscopy. [17] …”
Section: Introductionmentioning
confidence: 99%